Enablers of Multi-Currency Wallet Adoption : A TISM-Fuzzy MICMAC Approach - Singh, Ankita; Sahu, G. P. (Indian Journal of Marketing, 2025)
Purpose : This study investigated the essential elements that affect multi-currency wallet adoption among developing nations and established their relationships. It also analyzed the relationship between factors influencing consumer choices in cross-border digital payment transactions. Design/Methodology/Approach : Expert evaluation, literature review, and total interpretive structural modeling (TISM) have enabled researchers to develop and arrange critical enablers through a hierarchical structure. Fuzzy MICMAC analysis assessed the recognized enablers’ driving and dependence power relationships through multiple interpretation models. Findings : The research revealed 11 core factors: performance expectancy, perceived usefulness, effort expectancy, hedonic motivation, habit, ubiquity, facilitating conditions, social influence, perceived security, gamified payment, and behavioral intention. TISM demonstrated how the enablers were positioned at different levels of the hierarchy, yet Fuzzy MICMAC grouped them as dependent and independent linkage elements. Performance expectancy and perceived usefulness had the most significant influence on users; however, behavioral intention was the most influential factor. Practical Implications : This study presented valuable strategic recommendations for managers and developers regarding which enablement factors can boost multi-currency wallet usage. The study outcomes can help government officials create plans to improve digital payment systems in emerging markets while implementing educational initiatives. Originality/Value : We confirm that this study represents the initial research that merges TISM and fuzzy MICMAC for analzing expert opinions on multi-currency wallet adoption. Future research could build this work as a basis for empirical methodology development along with the creation of new policies.